Silicon dioxide core-shell microsphere and preparation method thereof

Through the polymerization modification and hydrolytic deposition technology on the surface of silica microspheres, the shell thickness and porosity of core-shell silica microspheres are accurately controlled, and the poor shell controllability and insufficient mechanical strength in the prior art are solved. The problem is that efficient high-pressure filling and separation is achieved.

CN119390077AInactive Publication Date: 2025-02-07NINGBO UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510005556.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing core-shell type silica microspheres have poor shell thickness controllability and low mechanical strength, making it difficult to meet the needs of high-pressure filling and separation.

Method used

The polyacrylamide gel layer is set by polymerization modification on the surface of the solid silica microspheres and depositing silica nanoparticles by hydrolysis and orthosilicate hydrolysis, the shell thickness and porosity are precisely controlled, thereby improving mechanical strength.

Benefits of technology

The precision and controllability of shell thickness and porosity is achieved, the mechanical strength of core-shell microspheres is significantly improved, and the high-pressure filling and separation process can be better withstand the high-pressure filling and separation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390077A_ABST
    Figure CN119390077A_ABST
Patent Text Reader

Abstract

The invention provides a silicon dioxide core-shell microsphere and a preparation method thereof, and the preparation method comprises the following steps: S1, taking acrylamide as a raw material, and polymerizing and modifying a polyacrylamide gel layer with a set thickness on the outer surface of a silicon dioxide solid microsphere; s2, dispersing the microspheres obtained in the step S1 in an aqueous solution, and adding a diamine organic compound to hydrolyze part of amido bonds of the polyacrylamide gel layer to form a poly organic amine gel layer; s3, the microspheres obtained in the step S2 are dispersed in an orthosilicate solution, orthosilicate is hydrolyzed in the poly organic amine gel layer, and silicon dioxide nanoparticles are deposited; and S4, calcining the microspheres obtained in the step S3 at high temperature, removing organic matters, and cross-linking silicon dioxide nanoparticles to obtain the silicon dioxide core-shell microspheres. According to the preparation method, the shell thickness and the shell porosity can be accurately controlled, and the mechanical strength of the whole core-shell microspheres can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of liquid chromatography separation materials, and in particular to a silicon dioxide core-shell microsphere and a preparation method thereof. Background Art

[0002] Core-shell silica fillers, also known as surface porous silica fillers, are composed of an internal solid core structure and an external porous shell structure. They were first proposed by Horvath et al. in the 1960s. Subsequently, due to their special structure, core-shell silica microspheres quickly attracted the attention of researchers. Dupont, Merck and Waters first developed the first generation of core-shell silica microspheres under the brands of Zipax, Perisorb and Corasil. In 2007, Advanced Material Technology Co., Ltd. in the United States developed the Halo chromatographic column, which is a 2.7μm core-shell silica microsphere formed by combining a 1.7μm solid core with a 0.5μm porous shell. Compared with fully porous silica microspheres of the same diameter, porous silica core-shell microspheres can shorten the mass transfer distance of the analyte in the stationary phase during chromatographic separation, reduce mass transfer resistance, and improve separation efficiency. The separation efficiency can be increased by more than double, and the chromatographic separation time can be shortened by more than half.

[0003] The prior art discloses a variety of methods for preparing core-shell silica microspheres, such as using urea-formaldehyde resin to electrostatically adsorb silica nanoparticles and then calcining them at high temperature to prepare core-shell silica microspheres; Patent CN201610655630.1 uses two quaternary ammonium salts with different carbon branch chain lengths as co-templates to prepare core-shell microspheres with a large radioactive mesoporous structure; Patent CN201810160294.2 uses silica polymer core-shell composite microspheres as templates and successfully prepares silica core-shell microspheres through a sol-gel process.

[0004] However, the existing preparation methods have the following problems: (1) The shell thickness is poorly controllable. Whether it is the urea-formaldehyde resin / silica gel nanoparticle self-assembly method or the radial mesoporous shell method, the shell thickness cannot be accurately controlled. (2) The mechanical strength of the shell is poor. The silica content in the shell of the urea-formaldehyde resin / silica gel nanoparticle self-assembly method is low, resulting in low mechanical strength. The core-shell silica is easily broken during high-pressure loading and subsequent high-pressure separation. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to develop a new core-shell silica microsphere preparation technology, which can accurately control the thickness of the shell layer and improve the overall mechanical strength of the microsphere.

[0006] To achieve the above object, the present invention provides a method for preparing silica core-shell microspheres, comprising the following steps: S1, using acrylamide as a raw material, polymerizing and modifying a polyacrylamide gel layer of a set thickness on the outer surface of the silica solid microspheres; S2, dispersing the microspheres obtained in step S1 in an aqueous solution, adding a diamine-based organic compound to hydrolyze part of the amide bonds of the polyacrylamide gel layer to form a polyorganic amine gel layer; S3, dispersing the microspheres obtained in step S2 in an orthosilicate solution, allowing the orthosilicate to hydrolyze in the polyorganoamine gel layer to deposit silicon dioxide nanoparticles; S4, calcining the microspheres obtained in step S3 at high temperature to remove organic matter, and cross-linking the silica nanoparticles to obtain silica core-shell microspheres.

[0007] The preparation method of the present invention first controllably grows a polyacrylamide gel layer on the surface of the solid silica microsphere, and then hydrolyzes the shell layer to accurately control the thickness and porosity of the shell layer. On the other hand, by increasing the amount of orthosilicate added, the content of silica in the shell layer can be increased, thereby improving the mechanical strength of the shell layer. Therefore, compared with the prior art, the preparation method of the present invention can significantly improve the accuracy of controlling the thickness and porosity of the shell layer, and improve the mechanical strength of the entire core-shell microsphere.

[0008] In a preferred or optional embodiment, in the step S1, the preparation method of the polyacrylamide gel layer is selected from atom transfer radical polymerization, free radical polymerization, and reversible deactivation radical polymerization, preferably atom transfer radical polymerization.

[0009] In a preferred or optional embodiment, in step S1, the diameter of the solid silica microspheres is 0.1-10 μm, and the thickness of the polyacrylamide gel layer is 1-1000 nm.

[0010] By utilizing surface atom transfer polymerization growth, the thickness of the polyacrylamide gel layer can be precisely controlled by simply quantitatively controlling the amount of acrylamide monomer and silica solid microspheres added.

[0011] In a preferred or optional embodiment, in step S2, the hydrolysis degree of the polyacrylamide gel layer is 10% to 90%.

[0012] In a preferred or optional embodiment, the molar ratio of the orthosilicate used in step S3 to the acrylamide used in step S1 is 0.1-2.0:1.

[0013] By controlling the hydrolysis degree of the polyacrylamide gel layer and the amount of orthosilicate added, the deposition amount of silica nanoparticles in the gel layer can be controlled, and ultimately the porosity of the shell layer can be controlled.

[0014] In a preferred or optional embodiment, in step S4, the calcination temperature is 300-1000° C. and the calcination time is 0.5-48 hours. The mechanical strength of the shell layer can be improved by selecting a suitable sintering temperature and sintering time.

[0015] In a preferred or optional embodiment, in step S2, the diamine organic compound is selected from one or more of ethylenediamine, propylenediamine, butylenediamine, pentanediamine, and hexamethylenediamine.

[0016] In a preferred or optional embodiment, in step S3, the orthosilicate is selected from one or more of methyl orthosilicate, ethyl orthosilicate, and isopropyl orthosilicate.

[0017] The present invention also provides a silica core-shell microsphere, which is prepared by the above preparation method and comprises a solid silica core layer and a porous silica shell layer. Preferably, the porosity of the porous silica shell layer is 10% to 90%. The silica core-shell microsphere of the present invention has the advantages of precise controllable shell thickness and porosity and high mechanical strength.

[0018] In summary, compared with the prior art, the present invention has the following beneficial effects: (1) The thickness of the shell layer is precisely controllable: a gel layer is controllably grown on the surface of the solid silica microspheres, and then the shell layer is prepared by hydrolysis. The thickness of the porous silica shell layer can be controlled by simply controlling the thickness of the polyacrylamide gel layer.

[0019] (2) The porosity of the shell layer is precisely controllable: By controlling the amount of orthosilicate and silica solid spheres modified with polyorganoamine gel layer added, the amount of silica nanoparticles deposited in the gel layer can be controlled, and ultimately the porosity of the shell layer can be controlled.

[0020] (3) High mechanical strength of the shell: Within a suitable porosity range, by increasing the amount of orthosilicate added, the content of silica in the shell can be increased, thereby improving the mechanical strength of the shell; by selecting a suitable sintering temperature and sintering time, the mechanical strength of the shell can also be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is an electron microscope image of the silica core-shell microspheres in Example 1.

[0022] Figure 2 This is a chromatogram of the reverse phase chromatography separation of alkylbenzenes using a silica core-shell microsphere chromatographic column in Example 2. DETAILED DESCRIPTION

[0023] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0024] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0025] The specific embodiment of the present invention provides a silica core-shell microsphere and a preparation method thereof to solve the problems of poor controllability of the shell thickness and poor mechanical strength of the shell of silica core-shell microspheres in the prior art. The preparation method comprises the following steps: S1. Using acrylamide as raw material, a polyacrylamide gel layer of a set thickness is polymerized and modified on the outer surface of solid silica microspheres.

[0026] In a specific embodiment, the preparation method of the polyacrylamide gel layer is selected from atom transfer radical polymerization, free radical polymerization, and reversible deactivation radical polymerization, preferably atom transfer radical polymerization.

[0027] In a specific embodiment, the diameter of the solid silica microspheres is selected to be 0.1-10 μm, and surface atom transfer polymerization is used for growth. The thickness of the polyacrylamide gel layer can be precisely controlled by quantitatively controlling the amount of acrylamide monomer and the solid silica microspheres added. The typical thickness of the polyacrylamide gel layer is 1-1000 nm.

[0028] S2, dispersing the microspheres obtained in step S1 in an aqueous solution, adding a diamine-based organic compound to hydrolyze part of the amide bonds of the polyacrylamide to form a polyorganic amine gel layer.

[0029] In a specific embodiment, the hydrolysis degree of the polyacrylamide gel layer can be controlled by controlling the relationship between the amount of the diamine organic compound added and the amount of the acrylamide monomer.

[0030] In a specific embodiment, the diamine organic compound can be selected from ethylenediamine, propylenediamine, butylenediamine, pentanediamine, hexamethylenediamine, etc. The hydrolysis temperature is controlled at 20-90° C., and the hydrolysis time is 1-24 hours. Preferably, the hydrolysis degree of the polyacrylamide gel layer is 10%-90%.

[0031] S3, dispersing the microspheres obtained in step S2 in an orthosilicate solution, allowing the orthosilicate to hydrolyze in the gel layer to deposit silicon dioxide nanoparticles.

[0032] By controlling the amount of orthosilicate added, the amount of silicon dioxide nanoparticles deposited in the gel layer can be controlled, and ultimately the porosity of the shell layer can be controlled. Within a suitable porosity range, by increasing the amount of orthosilicate added, the content of silicon dioxide in the shell layer can be increased, thereby improving the mechanical strength of the shell layer. In a specific embodiment, the molar ratio of orthosilicate to acrylamide is 0.1 to 2.0:1, preferably 0.4 to 1.0:1.

[0033] In a specific embodiment, the orthosilicate may be methyl orthosilicate, ethyl orthosilicate, isopropyl orthosilicate, etc. The hydrolysis is carried out at room temperature for 1 to 24 hours, preferably 1 to 100 hours, and preferably 12 to 64 hours.

[0034] S4, calcining the microspheres obtained in step S3 at high temperature to remove organic matter, and cross-linking the silica nanoparticles to obtain silica core-shell microspheres with porous silica as the shell layer.

[0035] In a specific embodiment, the calcination temperature is 300-1000° C. and the calcination time is 0.5-48 hours. The mechanical strength of the shell layer can be improved by selecting a suitable sintering temperature and sintering time.

[0036] The silica core-shell microspheres are prepared by the above method, including a solid silica core layer and a porous silica shell layer. The thickness and porosity of the shell layer are controllable. The porosity of the porous silica shell layer is typically in the range of 10% to 90%. The shell layer has high mechanical strength and can withstand high pressure, meeting the requirements of high-pressure filling and high-pressure separation.

[0037] The technical solutions and effects of the present invention are described below through specific embodiments.

[0038] Example 1

[0039] The core-shell silica microspheres were prepared as follows: (1) Prepare 10 mL of 70% methanol solution, add 1 g of (3-bromopropyl)triethoxysilane-modified solid silica microspheres with a diameter of 1.5 μm, add 0.2 g of acrylamide, and 0.02 g of N,N-methylenebisacrylamide; deoxygenate by bubbling with nitrogen for half an hour; add 0.1% by mass cuprous bromide and 0.1% initiator, seal and react at room temperature for 24 hours; collect the product, wash it with water, and dry it in a vacuum oven at 50°C to form a polyacrylamide gel layer with a thickness of 100 nm on the surface of the solid silica microspheres.

[0040] (2) The microspheres obtained in step (1) are dispersed in an aqueous solution, and the pH is adjusted to 7 with 0.1 M hydrochloric acid; 0.2 mL of 37% formaldehyde solution is added, and the mixture is reacted at room temperature for 3 h; then 0.6 mL of ethylenediamine is added and mixed, and the mixture is reacted at 50° C. for 12 h, and the hydrolysis degree of the polyacrylamide gel layer is 60%; the microspheres after the hydrolysis of the polyacrylamide are collected by centrifugation, washed with methanol and water until neutral, and dried in a vacuum oven at 50° C. to obtain silica microspheres modified with a polyacrylamide organic amine gel layer.

[0041] (3) The microspheres obtained in step (2) are dispersed in 10 mL of 60% ethanol solution, 0.4 mL of tetraethyl orthosilicate is added, and the mixture is reacted at room temperature for 48 h under mechanical stirring at 400 r / min. The microspheres after hydrolysis of tetraethyl orthosilicate are collected, washed with ethanol and water until neutral, and vacuum dried at 50° C. to obtain silica core-shell microspheres with silica nanoparticles deposited in the gel layer.

[0042] (4) The microspheres obtained in step (3) are placed in a muffle furnace, heated to 600°C at a heating rate of 2°C / min, maintained for 6 hours, and then slowly cooled to room temperature to obtain silica core-shell microspheres having a solid silica core layer and a porous silica shell layer.

[0043] The silicon dioxide core-shell microspheres prepared in this example were tested by electron microscopy, and the results were as follows: Figure 1 As shown, the shell thickness is 100nm, the porosity is 60%, and the core diameter is 1.5μm.

[0044] The silicon dioxide core-shell microspheres prepared in this example were subjected to nitrogen adsorption test. The specific surface area of ​​the microspheres was 50 m 2 / g, pore size is 8.5nm.

[0045] Example 2

[0046] The core-shell silica microsphere liquid chromatography column was prepared as follows: (1) Weigh 1 g of the silica core-shell microspheres prepared in Example 1, rinse with 6 M hydrochloric acid, pure water, and ethanol in sequence, and dry in a vacuum oven at 80° C. overnight.

[0047] (2) Collect the microspheres treated in step (1), add 20 ml of a 5% toluene solution of octadecyldimethylsilyl chloride, and add 5 ml of pyridine, place in an oven, and react at 100°C for 12 h.

[0048] (3) Repeat step (2) twice, collect the product, wash it, and vacuum dry it to obtain core-shell silica microspheres modified with a reverse phase chromatography stationary phase.

[0049] (4) The microspheres obtained in step (3) are dispersed in methanol and filled into a stainless steel column tube with an inner diameter of 2.1 mm and a tube length of 50 mm by a homogenization method at a pressure of 40 MPa to obtain a core-shell silica liquid chromatography column modified with a reverse phase chromatography stationary phase.

[0050] The core-shell silica liquid chromatography column prepared in Example 2 was used to separate five alkylbenzenes. The separation conditions were: acetonitrile / water (65:35), flow rate 0.2 mL / min, and detection wavelength 210 nm. The separation results are shown in Figure 2 As shown, the five compounds are toluene (1 in the figure), ethylbenzene (2 in the figure), propylbenzene (3 in the figure), butylbenzene (4 in the figure), and pentylbenzene (5 in the figure). The chromatographic dead time is about 1.5 minutes, and these alkylbenzene small molecules are effectively separated on the core-shell silica liquid chromatography column.

[0051] Example 3

[0052] The core-shell silica microspheres were prepared as follows: (1) Prepare 10 mL of 70% methanol solution, add 1 g of (3-bromopropyl)triethoxysilane-modified solid silica microspheres with a diameter of 2 μm, add 0.5 g of acrylamide, and 0.05 g of N,N-methylenebisacrylamide; deoxygenate by bubbling with nitrogen for half an hour; add 0.1% by mass cuprous bromide and 0.1% initiator, seal and react at room temperature for 24 hours; collect the product, wash it with water, and dry it in a vacuum oven at 50°C. A polyacrylamide gel layer with a thickness of 180 nm is formed on the surface of the solid silica microspheres.

[0053] (2) The microspheres obtained in step (1) are dispersed in an aqueous solution, and the pH is adjusted to 7 with 0.1 M hydrochloric acid; 0.2 mL of 37% formaldehyde solution is added, and the mixture is reacted at room temperature for 3 h; then 0.8 mL of ethylenediamine is added and mixed, and the mixture is reacted at 50° C. for 12 h, and the hydrolysis degree of the polyacrylamide gel layer is 40%; the microspheres after the hydrolysis of the polyacrylamide are collected by centrifugation, washed with methanol and water until neutral, and dried in a vacuum oven at 50° C. to obtain silica microspheres modified with a polyorganoamine gel layer.

[0054] (3) The microspheres obtained in step (2) are dispersed in 10 mL of 60% ethanol solution, 0.8 mL of tetraethyl orthosilicate is added, and the mixture is reacted at room temperature for 48 h under mechanical stirring at 400 r / min. The microspheres after hydrolysis of tetraethyl orthosilicate are collected, washed with ethanol and water until neutral, and vacuum dried at 50° C. to obtain silica core-shell microspheres with silica nanoparticles deposited in the gel layer.

[0055] (4) The microspheres obtained in step (3) were placed in a muffle furnace, heated to 800°C at a heating rate of 2°C / min, maintained for 4 h, and then slowly cooled to room temperature to obtain silica core-shell microspheres having a solid silica core layer and a porous silica shell layer.

[0056] The silica core-shell microspheres prepared in this example were tested by electron microscopy, and the shell thickness was 180 nm, the porosity was 40%, and the core diameter was 2 μm.

[0057] Example 4

[0058] The core-shell silica microsphere liquid chromatography column was prepared as follows: (1) Weigh 1 g of the silica core-shell microspheres prepared in Example 3, rinse with 6 M hydrochloric acid, pure water, and ethanol in sequence, and dry in a vacuum oven at 80° C. overnight.

[0059] (2) Collect the microspheres treated in step (1), add 20 ml of a 5% toluene solution of octadecyldimethylsilyl chloride, and add 5 ml of pyridine, place in an oven, and react at 100°C for 12 h.

[0060] (3) Repeat step (2) twice, collect the product, wash it, and vacuum dry it to obtain core-shell silica microspheres modified with a reverse phase chromatography stationary phase.

[0061] (4) The microspheres obtained in step (3) are dispersed in methanol and filled into a stainless steel column tube with an inner diameter of 2.1 mm and a tube length of 50 mm by a homogenization method at a pressure of 40 MPa to obtain a core-shell silica liquid chromatography column modified with a reverse phase chromatography stationary phase.

[0062] The core-shell silica liquid chromatography column prepared in Example 4 was used to separate five alkylbenzenes: toluene, ethylbenzene, propylbenzene, butylbenzene, and pentylbenzene. The separation conditions were acetonitrile / water (65:35), flow rate 0.2 mL / min, and detection wavelength 210 nm. The chromatographic dead time was about 1.6 min, and the alkylbenzene small molecules were effectively separated on the core-shell silica liquid chromatography column.

[0063] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A method for preparing silicon dioxide core-shell microspheres, characterized in that: The following steps are involved: S1, using acrylamide as a raw material, polymerizing and modifying a polyacrylamide gel layer of a set thickness on the outer surface of the silica solid microspheres; S2, dispersing the microspheres obtained in step S1 in an aqueous solution, adding a diamine-based organic compound to hydrolyze part of the amide bonds of the polyacrylamide gel layer to form a polyorganic amine gel layer; S3, dispersing the microspheres obtained in step S2 in an orthosilicate solution, allowing the orthosilicate to hydrolyze in the polyorganoamine gel layer to deposit silicon dioxide nanoparticles; S4, calcining the microspheres obtained in step S3 at high temperature to remove organic matter, and cross-linking the silica nanoparticles to obtain silica core-shell microspheres.

2. The method for preparing silicon dioxide core-shell microspheres according to claim 1, characterized in that: In the step S1, the preparation method of the polyacrylamide gel layer is selected from one of atom transfer radical polymerization, free radical polymerization, and reversible deactivation radical polymerization.

3. The method for preparing silicon dioxide core-shell microspheres according to claim 2, characterized in that: In the step S1, the diameter of the silica solid microspheres is 0.1-10 μm, and the thickness of the polyacrylamide gel layer is 1-1000 nm.

4. The method for preparing silicon dioxide core-shell microspheres according to claim 1, characterized in that: In the step S2, the hydrolysis degree of the polyacrylamide gel layer is 10% to 90%.

5. The method for preparing silicon dioxide core-shell microspheres according to claim 1, characterized in that: The molar ratio of the orthosilicate used in step S3 to the acrylamide used in step S1 is 0.1-2.0:

1.

6. The method for preparing silicon dioxide core-shell microspheres according to claim 1, characterized in that: In step S4, the calcination temperature is 300-1000° C., and the calcination time is 0.5-48 hours.

7. The method for preparing silica core-shell microspheres according to any one of claims 1 to 6, characterized in that: In the step S2, the diamine organic compound is selected from one or more of ethylenediamine, propylenediamine, butylenediamine, pentanediamine, and hexamethylenediamine.

8. The method for preparing silicon dioxide core-shell microspheres according to any one of claims 1 to 6, characterized in that: In step S3, the orthosilicate is selected from one or more of methyl orthosilicate, ethyl orthosilicate, and isopropyl orthosilicate.

9. A silicon dioxide core-shell microsphere, characterized in that: The silica gel is prepared by the preparation method as described in any one of claims 1 to 8, comprising a solid silica core layer and a porous silica shell layer.

10. The silica core-shell microspheres according to claim 9, characterized in that: The porosity of the porous silica shell layer is 10% to 90%.

Citation Information

Patent Citations

  • A kind of method for preparing mesoporous silica core-shell microspheres

    CN106276925B

  • Mesoporous silica particles

    CN101528603A

  • Preparation method for monodisperse hollow silicon dioxide nanosphere with controllable size and shell thickness

    CN103359743A

  • Method for preparing hollow mesoporous silica nano-spheres

    CN107140653A

  • Preparing method of macropore silicon dioxide core shell microspheres

    CN108341415A